Ganti Rugi Tanah Yang Tidak Tercapai Kesepakatan Antara Pemilik Dan Panitia Pelaksana.(Studi Pengadaan Tanah Untuk Pembangunan Proyek Jalan Tol Solo-Kertosono di Kabupaten Ngawi) - Hapsari, Nila Dwi; , Darsono, S.H., M.Hum (2017)
Problems of land acquisition is very vulnerable in handling, because it concerns the livelihood of many people, when seen from the government's need for land for development purposes, it is understandable that the state land available is limited, therefore the only way that can be achieved is by free the land owned by the community, both of which had been in control with rights under customary law or the rights of others according to the BAL. The land acquisition process will never escape with the issue of compensation, it is necessary diadakanpenelitian advance of any information and data submitted data in procuring indemnity estimates. If it has reached an agreement on the form and amount of compensation, then the newly made compensation payments followed by the release of rights over the land in question.